Fibre-coupled, multiplexed methane detection using range-resolved interferometry - Bremner, James; Kissinger, Thomas; Hodgkinson, Jane; Tatam, Ralph P. (Institute of Physics (IOP), 2021)
We describe the first use of range-resolved interferometric signal processing for measurement of spectral transmission. This was applied to gas sensing using tunable diode laser spectroscopy, allowing the simultaneous and independent measurement of methane concentrations in multiple gas cells. The system uses a single injection-current modulated diode laser and a single photodetector. For three gas cells, we show the ability of the system to measure methane at noise equivalent concentrations of less than 200 ppm for a 0.5 s measurement period and a potential noise equivalent concentration (1σ) of <20 ppm with 150 s averaging time. We further show that cross-talk between cells is below the experimental uncertainty for the system
Keywords: interferometry; multiplexed; multipoint; gas